(3Sja GdbVGI Ydi GdHZGIs - (3eMeO Hf SdjeGf Hf SYO Hf eSYhO GdcGajLj GdQhej GdMfaj, eMjj GdOjf, CHh YHO Gddg, J (B879 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdTQjYI efgGLkG ddYGdejf hHYO agPG Sja GdbVGI Ydi GdHZGI hJPcQI dChdi GdCdHGH s
(3BNQgG (B:s
(3aef MUd dg Cgdjg GdbVGA hTQhWg adG HCS HGdONhd ajg , dcf JQcg CMH Hd ChLH s
(3HgG fXGe GdJYbjHIs
(3efbhdg ef fSNI ecJhHI SfI (B964(3g`s
(3hgj efbhdI HOhQgG ef fSNI cJHgG GdeDda SfI (B868 (3g`s
(3cJHJ ahGJM GdcdGe HGdCMeQ s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3Gdabg GdESdGejs